Chemical composition and antimicrobial activity of the essential oil of Psidium guajava and Cymbopogon citratus - Bermúdez-Vásquez, María José (2019)
Introduction. The resistance of microorganisms to antibiotics is a public health problem that can affect livestock producers by having fewer options to treat animals in the event of a infection. Extracts of some plants with antimicrobial activity may represent an alternative to the use of antibiotics in livestock production. Objective. The objective of this work was to analyze the chemical composition and antimicrobial activity of the essential oils of guava leaves (Psidium guajava L.) and lemon grass (Cymbopogon citratus (DC.) Stapf) grown in Costa Rica and evaluate antimicrobial activity of P. guajava L. in meat and bone meal. Materials and methods. This research was developed at the Animal Nutrition Research Center (CINA) of the University of Costa Rica between March and October 2016. P. guajava leaves were collected from two different locations (San Pedro and Escazú) and those from C. citratus from the areas of Sarapiquí and Escazú. The extraction of the oils was done by hydrodistillation. The chemical composition was analyzed by gas chromatography and mass spectrometry. The antimicrobial capacity of the essential oils was evaluated by the disk diffusion test and the 96-well plate microdilution procedure. Results. The essential oils of C. citratus and P. guajava presented antimicrobial activity against the ten bacterial strains tested, being the gram positive bacteria the most sensitive to them. P. guajava oil from Escazú showed higher antimicrobial activity in vitro with respect to P. guajava oil from San Pedro and C. citratus oil. The oil of P. guajava had the ability to eliminate Escherichia coli that had previously been added to a matrix of meat and bone meal, but not to prevent colonization of it. Conclusion. According to the results of this research, the essential oils of lemon grass and guava leaf grown in Costa Rica, have an antimicrobial effect against bacteria relevant for feed safety and feed shelf life, future research is required to evaluate its applicability in animal feed.